PROFESIOGRAPHY AND PROFESIOGRAPHIC ANALYSES - HANZALOVÁ, Jana (Trends in education, 2008)
This report deals with theorethical definition of profesiography, profesiographic analyses, and is focused on profesiographic potentialities and usage. This report also involves the characteristic of operation analysis and methods needed to acquire important data about profession demands.
Keywords: profesiography; profesiographic analysis